Health of mobile pastoralists in the Sahel – assessment of 15 years of research and development. Issue 9 (9th July 2013) - Montavon, A.; Jean‐Richard, V.; Bechir, M.; Daugla, D. M.; Abdoulaye, M.; Bongo Naré, R. N.; Diguimbaye‐Djaibé, C.; Alfarouk, I. O.; Schelling, E.; Wyss, K.; Tanner, M.; Zinsstag, J.
Abstract In the Sahel, between Mauritania and Somalia including Northern Kenya, about 20–30 million people live as mobile pastoralists. The rhythm of their migration follows the seasons and the availability of resources such as water, pasture and salt. Despite their high exposure to zoonoses and problems caused by extreme climatic conditions, mobile pastoralists are virtually excluded from health services because the provision of social services adapted to their way of life is challenging. In cooperation with various partners in the region, the Swiss Tropical and Public Health Institute has been active in research and development in the Sahel for 15 years. Based on the perceived needs of mobile pastoralists and the necessities of development, interdisciplinary research has considerably contributed to better understanding of their situation and their problems. Close contact between humans and livestock necessitates close cooperation between human and animal health specialists. Such useful approaches should be continued and extended.